Grandmas at Bat - McCully, Arnold Emily; Nang ChanYeema (New York, USA HarperCollins Publisher, Inc., 1993)
Pip's two grandmothers, who cannot agree on anything, take over coaching her baseball team and create chaos.
Keywords: Level Books